Age specific incidence of five major cancers in Nepal, 2012 - Poudel, Krishna Kanta; Huang, Zhibi; Neupane, Prakash Raj (Nepal Journal of Epidemiology, 2016)
Background: Population based cancer registry is inevitable to measure the indicators of cancer. This retrospective study was conducted to perform the age specific incidence and age standardized rate of cancer by sex, age and sites in Nepal, 2012. Materials and Methods: The data collected by hospital based National cancer registry programme of Nepal were used to calculate the age specific incidence of five major cancers by sex and sites. The age standardized rate of ten major cancers, both in males and females of 2012 was also performed. Results: The 70-74 years age group had the highest incidence rate (188.08) for men while for women the age group of 65-69 years had the highest incidence (140.61) per 100,000. For male, lung cancer had the highest incidence rate (4.45) whereas bladder had the lowest rate (0.98). Similarly for female, Cervix Uteri cancer had the highest incidence rate (5.35) whereas stomach had the lowest (1.06). Conclusion: This study presented that cancer was increased with age both in males and females. The leading cancer in males was bronchus and lung while in females it was cervix uteri.